Dietary macronutrient recommendations for optimal recovery post-exercise: Part II - Wright, H. H.; Claassen, A.; Davidson, J. (South African Journal of Sports Medicine, 2004)
A net positive nitrogen balance is needed for exerciseinduced muscle damage to be repaired during the recovery period. Apart from hormones and growth factors, adequate energy and amino acid availability contribute to this balance and influence the rate at which protein synthesis and muscle repair occur post-exercise. This paper reviews the dietary factors involved in muscle repair during the post-exercise recovery period. Both resistance and endurance-trained athletes have a higher dietary protein requirement of between 1.2 and 1.8 g protein/kg body weight (BW)/day, with an upper limit of 2 g protein/kg BW/day. To increase the rate of protein synthesis during the recovery period, immediate ingestion of protein postexercise is recommended. Additionally, ingesting 1.2 g carbohydrate (CHO)/kg BW/hour with 0.4 g/kg BW/hour of a wheat amino acid mixture (wheat protein hydrolysate combined with free leucine and phenylalanine) enhances the insulin response compared with ingesting CHO only or combined with other protein hydrolysates, peptides, or intact protein. This increased insulin response could increase muscle protein synthesis indirectly by altering the hormonal milieu. Results on the anabolic effect of single or mixtures of amino acids remains to be further elucidated. The possible antioxidant benefits of whey protein supplementation in athletes remains to be proven, while the antioxidant potential of soy protein holds promise. The effect of glutamine supplementation on protein synthesis in athletes is limited and its clinical relevance for enhanced immune function in endurance athletes remains to be established. Creatine supplementation seems to be beneficial in terms of protein synthesis and gains in fat free mass during the recovery period, while the use â-hydroxy â-methylbutyrate (HMB) supplementation by trained athletes seems to have limited benefits. It is important to keep dietary advice individualised considering the complexity in which the endocrine system regulates cell function, the diverse mechanisms that control homeostasis, as well as genetic variability.